The meaning of work and career as calling: a model to determine millennial's career satisfaction / Selly Septianingsih and Olivia Fachrunnisa - Septianingsih, Selly; Fachrunnisa, Olivia (Universiti Teknologi MARA, Perlis, 2021)
This research aims to examine and analyze the meaning of work and career as a calling to determine career satisfaction in the millennial workforce. A career as a calling is an opportunity to create social work in the work environment. It is correlated to life satisfaction and meaning, career decisions, self-identity, and positive effectiveness. Meanwhile, the meaning of work for millennials is about the meaning of life. The millennial generation prefers to get freedom according to their characteristics and passions. Job satisfaction lies in self-actualization at work that does not only seek financial stability. The research was conducted using quantitative methods, data were collected from questionnaires and analyzed using partial least square (PLS). The sample population of this study comprised 150 millennial lecturers of Islamic universities in Semarang, Indonesia. The criteria were those aged 20-40 years old with a minimum working period of one year. The results showed that digital fluency and spiritual work value positively and significantly affect the meaning of work and career as a calling. Meanwhile, the meaning of work and career as a calling has a positive and significant effect on career satisfaction.